Game Edukasi Berbasis Augmented Reality (AR) Menggunakan Metode Marker-Based Tracking dalam Perancangan Aplikasi Tata Surya - Aryani, Diah; Noviandi, Noviandi; Fatonah, Nenden Siti; Akbar, Habibullah (Yayasan Kita Menulis, 2024)
Augmented Reality (AR) technology has had a positive impact on education, particularly in improving the quality of learning and creating an interactive learning environment. This research aims to design a solar system application based on AR as an alternative learning media that integrates 3D models, animations, and videos to enhance the learning experience of students, especially at SDN Larangan 5 Tangerang. The background of this research is the lack of variety in teaching the solar system material at the school, which still relies on textbooks and videos without utilizing AR technology. The method used in this study is Marker-Based Tracking, which involves the use of specific markers to detect objects and display information as well as 3D models of the planets in the Solar System on the device screen. By using this method, the application provides a more interactive and immersive learning experience. For usability testing, the System Usability Scale (SUS) method was used, involving 33 respondents, including teachers, students, and parents. The test results yielded a score of 78, indicating a high level of user satisfaction with the application. This study is expected to be a first step in the application of AR technology to support learning innovation, particularly in enhancing students' understanding of the solar system concept